Are Adolescent Cigarette Smokers Who Use Smokeless Tobacco More Likely to Continue Smoking in the Future than Cigarette-Only Smokers: Results from Waves I and II of the Adolescent Health Survey. (26th March 2012) - O'Hegarty, Michelle M.; Pederson, Linda L.; Asman, Katherine J.; Malarcher, Ann M.; Mirza, Sara A.
Abstract : We explored whether dual use of smokeless and cigarettes among adolescents predicts continued smoking. Data came from Waves I (1994-95) and II (1996) of the National Longitudinal Study of Adolescent Health, using information from 3, 284 Wave I current smokers. Multivariate models were used to assess whether use of smokeless tobacco at Wave I was associated with continuation of cigarette smoking at Wave II, controlling for possible confounders. The prevalence of current cigarette smoking at Wave 1 was 27.9%; among this group of adolescents and young adults, 14.5% also used smokeless tobacco. At Wave II, 73.6% of dual product users and 78.4% of cigarette-only users in Wave I reported continued smoking (O R = 0.71 [95% CI 0.52–0.98]). Combined use of cigarette and smokeless tobacco does not appear to be related to continued smoking one year later. Longer-term followups are needed to determine the stability of this relationship for ≥1 year.